Inspiration and Interpretation: A Theological Introduction to Sacred Scripture - Thurston, Bonnie Bowman (Cistercian studies quarterly, 2012)
The article reviews the book "Inspiration and Interpretation: A Theological Introduction to Sacred Scripture," by Denis Farkasfalvy.